2015
DOI: 10.1021/acs.jpca.5b06831
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CH···O, SH···O, Chalcogen, and Tetrel Bonds Formed by Neutral and Cationic Sulfur-Containing Compounds

Abstract: The ability of neutral and charged S-compounds to form different sorts of noncovalent bonds is examined by ab initio calculations. Neutrals are represented by CH3SH and fluoro-substituted FSCH3; cations are (CH3)3S(+), CH3SH2(+), and FHSCH3(+). Each is paired with N-methylacetamide (NMA) whose O atom serves as a common electron donor. Charged species engage in much stronger noncovalent bonds than do the neutral molecules, by as much as an order of magnitude. The strongest noncovalent bond for any system is a O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 98 publications
4
74
0
Order By: Relevance
“…[58][59][60][61][62][63] To ensure the structures obtained were minima on the potential energy surface, frequency calculations were also performed at the same level, affirming all structures have no imaginary frequencies. [58][59][60][61][62][63] To ensure the structures obtained were minima on the potential energy surface, frequency calculations were also performed at the same level, affirming all structures have no imaginary frequencies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[58][59][60][61][62][63] To ensure the structures obtained were minima on the potential energy surface, frequency calculations were also performed at the same level, affirming all structures have no imaginary frequencies. [58][59][60][61][62][63] To ensure the structures obtained were minima on the potential energy surface, frequency calculations were also performed at the same level, affirming all structures have no imaginary frequencies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Despite any barriers to their formation, these tetrel bonds occur widely and are of great import in a number of chemical and biological processes. [35][36][37][38][39][40][41][42] The scale and effects of the geometric deformation of the TR 4 molecule required to accommodate a Lewis base have been assessed quantitatively. [9,10] Scores of tetrel bonds have been identified within protein structures, [11][12][13][14][15] and are implicated in the catalytic process of several enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for thed irectionality of YBs comes from variouss tudies of intermolecular interactions involving sulfur. [56,61] S···O, S···N, and S···S YBs involving methionine andc ysteine have been identified in proteins,a nd it has been suggested that they mayp romote protein folding and stability. [49,[52][53][54][55][56][57][58][59][60] Theoretical calculations have suggestedt hat the strength of the YB between neutral systemsi sc omparable to that of aw eak HB, [39] whereas some interactions involving ac halcogen cation can have very high interaction energies.…”
Section: Introductionmentioning
confidence: 99%